N-myc downstream regulated gene 1 modulates Wnt-β-catenin signalling and pleiotropically suppresses metastasis - Liu, Wen (WILEY-VCH Verlag, 2012)
Wnt signalling has pivotal roles in tumour progression and metastasis; however, the exact molecular mechanism of Wnt signalling in the metastatic process is as yet poorly defined. Here we demonstrate that the tumour metastasis suppressor gene, NDRG1, interacts with the Wnt receptor, LRP6, followed by blocking of the Wnt signalling, and therefore, orchestrates a cellular network that impairs the metastatic progression of tumour cells. Importantly, restoring NDRG1 expression by a small molecule compound significantly suppressed the capability of otherwise highly metastatic tumour cells to thrive in circulation and distant organs in animal models. In addition, our analysis of clinical cohorts data indicate that Wnt+/NDRG−/LRP+ signature has a strong predictable value for recurrence-free survival of cancer patients. Collectively, we have identified NDRG1 as a novel negative master regulator of Wnt signalling during the metastatic progression, which opens an opportunity to define a potential therapeutic target for metastatic disease.